A Critical Analysis and Review of the Book Photography: A Middle-Brow Art - Morteza Sedighifard; Hedie Khazaei; Mehdi Moghimnejad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This research is based on a structured analysis of the book written by Pierre Bourdieu, called Photography, a Middle-Brow Art. This study is a descriptive analysis of the different sections of the book from different perspectives. In this research, we considered the Persian translation of the book. Moreover, the origin of the work and the effectiveness of its contents after more than half a century from its publication, along with its advantages and disadvantages were discussed. We also compared the Persian translation to the English version. The translation of the work was also examined, which revealed that the book has a decent translation quality, despite detecting a few errors in some sections. It can be concluded that due to the long time since its publication and the speed of change in its concerning fields, namely sociology and photography, most arguments in the book can no longer be cited. Also, because the book contains discontinuous articles and does not have an explicit conclusion, it does not have the desired unity in general, which might result in the fact that each section can be read independently.